1996
DOI: 10.1016/0895-7061(96)00098-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin on renal sodium and uric acid handling in essential hypertension

Abstract: In normal subjects, insulin decreases the urinary excretion of sodium, potassium, and uric acid. We tested whether these renal effects of insulin are altered in insulin resistant hypertension. In 37 patients with essential hypertension, we measured the changes in urinary excretion of sodium, potassium, and uric acid in response to physiological euglycemic hyperinsulinemia (by using the insulin clamp technique at an insulin infusion rate of 6 pmol/min/kg). Glucose disposal rate averaged 26.6 +/- 1.5 mumol/min/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
154
1
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(170 citation statements)
references
References 33 publications
6
154
1
9
Order By: Relevance
“…These findings closely agree with a recent study that found that both caffeinated and decaffeinated coffee were inversely associated with C peptide levels (a marker of endogenous insulin levels), but tea intake and total caffeine intake after adjusting for coffee intake were not (7). Because there is a strong positive relationship between serum insulin resistance and hyperuricemia (23)(24)(25)(26)(27) and insulin reduces the renal excretion of urate (25,28,29), decreased insulin resistance and insulin levels associated with coffee consumption may lead to lower uric acid levels.…”
supporting
confidence: 90%
“…These findings closely agree with a recent study that found that both caffeinated and decaffeinated coffee were inversely associated with C peptide levels (a marker of endogenous insulin levels), but tea intake and total caffeine intake after adjusting for coffee intake were not (7). Because there is a strong positive relationship between serum insulin resistance and hyperuricemia (23)(24)(25)(26)(27) and insulin reduces the renal excretion of urate (25,28,29), decreased insulin resistance and insulin levels associated with coffee consumption may lead to lower uric acid levels.…”
supporting
confidence: 90%
“…The hyperinsulinaemia associated with the latter may stimulate sodium and UA absorption from the proximal tubule. 31 However, several studies suggest that SUA may be directly linked with HT. Analysis of a cohort of male workers in southern Italy 32 showed a positive association between UA and the development of HT independent of age, BMI and lipids; similar results (controlled for body-weight, serum creatinine, alcohol consumption, parental history of HT, excessive salt intake and truncal fat) were also reported in a cohort of the Kaiser Permanente Medical Care Programme.…”
Section: Discussionmentioning
confidence: 99%
“…Fasting insulin levels inversely correlate with urinary uric acid clearance and are positively associated with serum uric acid in healthy subjects [28]. Furthermore, exogenously administered insulin decreases urinary excretion of uric acid and this is mediated by stimulating urate reabsorption [33] in healthy subjects as well as in hypertensive patients [33]. These studies suggest that the renal proximal tubule remains sensitive to the effects of insulin even in subjects with hypertension (who are often insulin resistant).…”
Section: Metabolic Syndrome Renal Disease and Uric Acidmentioning
confidence: 94%